Coaker film rushes : silent images of Port Union, 1970's - Memorial University of Newfoundland. Extension Service (Producer) (Memorial University of Newfoundland. Extension Service, 1970)
Silent footage of Port Union, Newfoundland: the harbour,fish plant, Power house; bust of Willam F. Coaker Coaker R-14-P Condition: Silent Film